Seedling Performance, Growth and Yield of Onion Sown by Direct Seeding in Tropical Riparian Soil - Rina Sopiana; R.A. Suwignyo; M. Umar Harun; Susilawati Susilawati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The objective of this study was to obtain a seed-origin onion (Allium cepa L.) that was able to grow in the tropical riparian soil. Research designed with non-experimental. Two cultivars were studied, namely Sanren and Lokananta. Onion seeds were planted directly without transplanting, there were three plots (4 m x 1.6 m x 0.3 m) and three germination testplot (1 m x 1.6 m x 0.3 m). Soil tillage, spacing/ population, fertilization, plant maintenance and pest-diseases control in accordance with the recommendations. Research result obtained Sanren had higher germination (94.40%) and vigor index (60.60) then Lokananta. The growth of two onion cultivars showed good performance because there was no transplanting. Almost all the the variables for seedlings, vegetative organs and bulbs were significantly different between two cultivars. From the boxplot test, it was found that the data were of symmetry for Sanren (number stems, dry weight of leaves, and dry weight of bulb), and the Lokananta cultivar (vigor index, number of stems, number of bulbs, plant height and leaf dry weight). There was a significant correlation for Sanren (plant height with bulbs weight and number of roots), and Lokananta cultivars (number of roots with number of stems and leaf dry weight). Fresh bulbs weight per clump from Sanren (46.71 g) and Lokananta (17.84 g).